Відновлення соціальних навичок за допомогою фізичної активності у студентів, які пережили стресові ситуації - Церетелі, Вікторія Олександрівна; Ширяєва, Світлана Вікторівна; Кучеренко, Григорій Григорович (Український державний університет імені Михайла Драгоманова, 2025)
У статті розглянуто питання відновлення соціальних навичок за допомогою фізичної активності у студентів, які пережили стресові ситуації. Дослідження проводилося серед 150 студентів, поділених на дві групи: експериментальну (група А), яка проходила програму фізичної активності, та контрольну (група Б), що не мала спеціальних фізичних занять. Протягом двох місяців студенти групи А самостійно виконували обрані фізичні вправи (командні ігри, плавання, парні тренування) та брали участь у психофізичних онлайн-тренінгах. Результати показали значне покращення комунікативних навичок, зниження рівня тривожності та підвищення самооцінки у студентів групи А. Контрольна група також мала певний прогрес, але значно нижчий. Висновки підтверджують ефективність фізичної активності як засобу соціальної адаптації, що особливо важливо в сучасних умовах. Подальші дослідження можуть бути спрямовані на розширення методик фізичної активності для студентів різних категорій.

The article examines the issue of restoring social skills in students who have experienced stressful situations through physical activity. In modern conditions, Ukrainian students face numerous stressful situations caused by military actions, economic difficulties, social instability and other challenges. Loss of social skills, reduced communication and isolation are the consequences of experienced stress, which negatively affects their psycho-emotional sphere and the educational process. In such a situation, physical activity can become an important tool for the restoration of social skills and contribute to the adaptation of students to the educational environment and social life. The study was conducted among 150 students divided into two groups: an experimental group (Group A), which participated in a physical activity program, and a control group (Group B), which did not engage in any special physical exercises. Over two months, students in Group A independently performed selected physical activities (team sports, swimming, paired training) and participated in psychophysical online training sessions. The purpose of the study. Determining the effectiveness of physical activity in restoring social skills in students who have experienced stressful situations, as well as developing recommendations for the use of physical activity for social rehabilitation. Methodology: analysis of scientific literature, student questionnaires, pedagogical experiment, methods of mathematical statistics. The results showed significant improvements in communication skills, reduced anxiety levels, and increased self-esteem among students in Group A. The control group also demonstrated some progress, but to a significantly lesser extent. The findings confirm the effectiveness of physical activity as a means of social adaptation, which is particularly important in today's conditions. Further research may focus on expanding physical activity methodologies for different categories of students.
Restoring social skills through physical activity in students who have experienced stressful situations
Keywords: фізична активність; соціальні навички; стресові ситуації; студенти; адаптація; комунікація; психоемоційний стан; physical activity; social skills; stressful situations; students; adaptation; communication; psycho-emotional state